Method for synchronously recovering lithium, copper, cobalt, nickel and manganese in waste ternary lithium battery

By using sodium chloride solution and calcium chloride to reduce, melt and leaching and extraction during the recycling process of waste lithium batteries, the problems of long recycling processes and high economic costs in the existing technology are solved, and lithium, copper, cobalt, Synchronous and efficient recycling of nickel and manganese.

CN119464720APending Publication Date: 2025-02-18CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411626745.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art has the disadvantages of long recycling processes, high economic costs and failure to recover lithium simultaneously when recycling lithium, copper, cobalt, nickel and manganese in waste lithium batteries.

Method used

After discharge of the used lithium battery in saturated sodium chloride solution, disassemble and mix it with ball mill, add calcium chloride, quartz and limestone for reduction and smelting, collect smoke and alloy phases, and leaching and extraction respectively to achieve lithium and copper , synchronous recycling of cobalt, nickel and manganese.

Benefits of technology

The synchronous recycling of lithium, copper, cobalt, nickel and manganese is achieved, which shortens the recycling process, reduces economic costs, and is simple in the process, which is suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464720A_ABST
    Figure CN119464720A_ABST
Patent Text Reader

Abstract

The invention discloses a method for synchronously recovering lithium, copper, cobalt, nickel and manganese in a waste ternary lithium battery, which comprises the following steps of: carrying out reduction smelting on the waste ternary lithium battery in a smelting furnace, adding calcium chloride, limestone and quartz stone in the reduction smelting process for slagging, and reducing copper, cobalt and nickel elements in a battery material into an alloy; lithium and manganese elements are converted into volatile lithium chloride and manganese chloride in the smelting process, the volatile lithium chloride and manganese chloride enter a gas phase to be collected, and then lithium carbonate and manganese hydroxide are prepared through a water washing-sodium hydroxide precipitation-sodium carbonate precipitation method. According to the method, synchronous recovery of lithium, nickel, cobalt, copper and manganese is achieved, and compared with an existing wet treatment process, the treatment capacity is larger, pretreatment is simpler, the recovery technological process is shortened, and the economic cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of pyrometallurgy, and specifically relates to a method for synchronously recovering lithium, copper, cobalt, nickel and manganese from waste ternary lithium batteries. Background Art

[0002] With the rapid development of my country's new energy vehicle industry, the recycling of retired lithium batteries has become increasingly important. The average life of lithium batteries is usually 5 to 8 years. It is estimated that the theoretical recycling volume of waste lithium-ion batteries in my country will reach 2.312 million tons in 2026. The recycling of waste lithium batteries is of great significance to the implementation of my country's sustainable development strategy. In terms of environmental protection, lithium battery recycling can prevent the pollution of the environment by toxic substances such as heavy metals and fluorides contained in them. In terms of strategic resources, my country's nickel, cobalt, lithium and other resources are relatively scarce, and the import rates are as high as 60%, 95% and 80% respectively. The content of lithium, copper, cobalt, nickel and manganese in waste lithium batteries is much higher than the grade in the original ore. Therefore, the recycling of valuable metals in waste lithium batteries is an important way to solve the shortage of related resources in my country, and it is also of great strategic significance to promote the sustainable development of my country's new energy vehicle industry.

[0003] The main methods for recycling and treating waste lithium batteries include wet treatment and pyrometallurgy. The wet recycling process of waste lithium batteries includes the pretreatment of waste lithium batteries (discharging, crushing and screening, separation of electrode materials), leaching process, separation and purification of valuable metals in the leachate (solvent extraction, precipitation, electrolysis, ion exchange and salting out), etc. Hydrometallurgical technology can recover most of the components in lithium batteries, but the process has the disadvantages of long recycling process and high economic cost.

[0004] The traditional pyrometallurgical treatment is to directly reduce and smelt the waste lithium batteries in a smelting furnace, eliminating the waste battery pretreatment process. The plastic, organic solvent and graphite in the battery are burned to provide heat. At the same time, the aluminum box graphite can be used as a reducing agent. Then limestone and quartzite are added to make slag, and slag containing aluminum, silicon, calcium, manganese and iron and alloys containing copper, cobalt, nickel and a small amount of iron can be smelted. Then, the obtained alloy is leached with sulfuric acid and solvent extraction to recover copper, cobalt and nickel respectively. For example, patent CN103526035B uses waste lithium batteries or / and smelting slag containing copper, cobalt and nickel to smelt together. This method uses an alkaline slag system, and the recovery rates of the obtained alloy copper, cobalt and nickel are all ≥95%, and the contents of copper, cobalt and nickel in the slag are all ≤0.5wt.%. This method has good benefits for the recovery of copper, cobalt and nickel, but does not involve the recovery of lithium. Lithium basically enters the slag and requires a separate wet process to recover it. Patent CN113061725A proposes a method for recovering lithium from the pyrometallurgical treatment of waste lithium batteries, which specifically uses additives to volatilize lithium elements in the form of lithium chloride into the gas phase, and recovers Cu-Fe-Co alloy at the same time. This method can recover lithium elements, but the resulting alloy contains 60-70% iron, which affects the separation and recovery of copper and cobalt, and the method does not mention the recovery of nickel. Summary of the invention

[0005] The object of the present invention is to provide a method for simultaneously recovering lithium, copper, cobalt, nickel and manganese from waste ternary lithium batteries.

[0006] The present invention provides a method for synchronously recovering lithium, copper, cobalt, nickel and manganese from waste ternary lithium batteries, comprising the following steps:

[0007] S1. The waste lithium battery is immersed in a saturated sodium chloride solution and discharged, and then disassembled, crushed and ground to obtain waste battery raw materials;

[0008] S2. The waste battery raw material and the preset amount of calcium chloride, quartz stone, and limestone are ball-milled to obtain a mixture;

[0009] S3. The mixture is heated and smelted in a protective gas atmosphere, and smoke, alloy phase and slag phase are collected;

[0010] S4. dissolving and leaching the smoke using distilled water, and filtering to obtain a leachate and a leach residue;

[0011] S5. The leachate is heated, sodium hydroxide is added, and manganese hydroxide precipitate is obtained by filtration, and sodium carbonate is added to the filtrate, and lithium carbonate precipitate is obtained by filtration;

[0012] S6. Grind the alloy phase, digest it with hydrochloric acid and nitric acid, and then use extractants to extract copper ions and nickel and cobalt ions in the solution respectively.

[0013] Furthermore, in step S1, the waste lithium batteries include NMC111, NMC622, NMC532, and NMC811 waste lithium batteries.

[0014] Furthermore, in step S2, the preset usage amount of calcium chloride is 2 to 3 times the sum of the molar numbers of lithium and manganese in the raw materials; the calcium chloride is an industrial grade reagent;

[0015] Quartz and limestone are added to make slag for the subsequent smelting step. Quartz and limestone are added in a ratio of 40-60% by weight of calcium oxide, 35-45% by weight of silicon oxide, and 8-12% by weight of aluminum oxide according to a calcium-silicon-aluminum slag system.

[0016] Furthermore, in step S3, the protective gas is argon gas with a flow rate of 100 mL / min; the process conditions of the heating and smelting are: the smelting temperature is 1400-1600°C, the holding time is 80-150 min, and the heating rate is 5-10°C / min; after the heating and smelting is completed, it is cooled to room temperature at a cooling rate of 5-10°C / min, and the smoke, alloy phase and slag phase are collected.

[0017] Furthermore, the slag phase is glassy, ​​wherein the contents of lithium, copper, cobalt, nickel and manganese metals are all less than or equal to 0.5wt.%, meeting the standards for making glass raw materials for building materials.

[0018] Furthermore, in step S4, the liquid-to-solid ratio of smoke and distilled water is (5-15):1, and the liquid-to-solid ratio is the ratio of liquid volume mL to solid mass g; the process conditions of the dissolution and leaching are: reaction temperature of 20-40°C, stirring rate of 400-800rpm, and reaction time of 1-2h.

[0019] Furthermore, the step S5 is specifically as follows: heating the leachate to 80-90° C., then adding sodium hydroxide to adjust the pH value to a pH greater than 12, filtering to obtain a manganese hydroxide precipitate and a filtrate; and then adding a saturated sodium carbonate solution to the filtrate, filtering to obtain a lithium carbonate precipitate after sufficient reaction.

[0020] Furthermore, in step S6, the extractant for copper ions is one or more of ketoximes or aldoximes; the extractant for nickel and cobalt ions is one or more of organic phosphine or amines.

[0021] Beneficial effects of the present invention:

[0022] (1) The method of the present invention adds calcium chloride during the reduction smelting process, which can convert lithium and manganese into volatile lithium chloride and manganese chloride that enter the gas phase, and simultaneously prepare copper-cobalt-nickel alloy, thereby achieving the simultaneous recovery of lithium, nickel, cobalt, copper and manganese;

[0023] (2) Compared with the wet treatment process, the method of the present invention has the advantages of large processing capacity and simple battery pretreatment, shortening the recycling process and reducing economic costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic diagram of the process of the present invention. DETAILED DESCRIPTION

[0025] In order to make the application method and effect of the present invention clearer, the embodiments of the present invention will be described in detail below.

[0026] Example 1

[0027] A waste lithium battery cell with a positive electrode material of NMC111 was discharged, disassembled, crushed and ground to obtain 39.0g of material (weight percentage (wt.pct) in the material: Li 0.88, Mn 2.40, Cu 5.56, Co 2.50, Ni 2.51). This material (the weight of aluminum in the material is 7.6g as alumina) was ball-milled with 25.9g of calcium chloride powder, 30.2g of quartz powder and 15.0g of calcium oxide powder (the weight of calcium oxide in the slag system accounted for 42.6%, the weight of silicon oxide accounted for 45.9%, and the weight of aluminum oxide accounted for 11.5%) to obtain 110.1g of a mixture. The mixture was placed in a tubular furnace for heating at a heating rate of 5°C / min, and reduction smelting was carried out at a temperature of 1400°C and an argon atmosphere for 80 minutes. After the reaction was completed, the cooling rate was 5°C / min, and it was cooled to room temperature. The sample was taken out to obtain 11.6g of alloy and 66.5g of slag respectively. 32.0g of smoke dust obtained by volatilization was collected on the inner wall of the reaction tube. The smoke dust was dissolved and leached with 200mL of distilled water. The reaction temperature of the dissolution and leaching was 20°C, the stirring rate was 400rpm, and the reaction time was 1 hour. Then the solution was heated to 80°C, 0.8g of sodium hydroxide was added to a pH value of 13, and manganese hydroxide precipitate was obtained by filtration. Saturated sodium carbonate solution was continued to be added, and lithium carbonate precipitate was obtained by filtration after sufficient reaction.

[0028] The main components of the alloy are in weight percentage (wt.pct): Cu 49.1, Co 22.5, Ni 21.4. The metal recovery rate is calculated to be: Cu 93%, Co 95%, Ni 90%. The main component of the obtained slag is calcium aluminum silicate, presenting a glassy slag phase, and the contents of Li and Mn in the slag are both less than 0.05wt.pct.

[0029] 4.1 g of manganese hydroxide was obtained by precipitation, and the calculated recovery rate of manganese was 96%; 5.0 g of lithium carbonate was obtained by precipitation, and the calculated recovery rate of lithium was 98%.

[0030] Example 2

[0031] A waste lithium battery cell with a positive electrode material of NMC811 was discharged, disassembled, crushed and ground to obtain 40.0g of material (weight percentage (wt.pct) in the material: Li 0.93, Mn 0.71, Cu 7.03, Co 0.71, Ni 5.46). This material (the weight of aluminum in the material is 7.7g as alumina) was ball-milled with 19.1g of calcium chloride powder, 30.9g of quartz powder and 19.2g of calcium oxide powder (the weight of calcium oxide in the slag system accounted for 42.7%, the weight of silicon oxide accounted for 45.8%, and the weight of alumina accounted for 11.5%) to obtain 109.2g of a mixed material. The mixture was placed in a tubular furnace for heating at a heating rate of 10°C / min, and reduction smelting was carried out at a temperature of 1450°C and an argon atmosphere for 120 minutes. After the reaction was completed, the cooling rate was 10°C / min, and the mixture was cooled to room temperature. The sample was taken out to obtain 13.9g of alloy and 66.9g of slag, respectively. 28.4g of smoke dust obtained by volatilization was collected on the inner wall of the reaction tube. The smoke dust was dissolved and leached with 200mL of distilled water. The reaction temperature of the dissolution and leaching was 30°C, the stirring rate was 600rpm, and the reaction time was 1.5 hours. The solution was then heated to 85°C, 0.8g of sodium hydroxide was added to a pH value of 13, and manganese hydroxide precipitate was obtained by filtration. Saturated sodium carbonate solution was continued to be added, and lithium carbonate precipitate was obtained by filtration after sufficient reaction.

[0032] The main components of the alloy are calculated by weight percentage (wt.pct): Cu 50.8, Co 5.3, Ni 39.9. The metal recovery rate is calculated to be: Cu 92%, Co 95%, Ni 93%. The main component of the obtained slag is calcium aluminum silicate, presenting a glassy slag phase, and the content of Li and Mn in the slag is less than 0.05wt.pct.

[0033] 1.2 g of manganese hydroxide was obtained by precipitation, and the calculated recovery rate of manganese was 95%; 5.2 g of lithium carbonate was obtained by precipitation, and the calculated recovery rate of lithium was 97%.

[0034] Example 3

[0035] A waste lithium battery cell with a positive electrode material of NMC622 was discharged, disassembled, crushed and ground to obtain 37.5g of material (weight percentage (wt.pct) in the material: Li 0.91, Mn 1.42, Cu 6.22, Co 1.39, Ni 4.44). This material (the weight of aluminum in the material is 7.3g as alumina) was ball-milled with 20.9g of calcium chloride powder, 29.0g of quartz powder and 16.5g of calcium oxide powder (the weight of calcium oxide in the slag system accounted for 42.7%, the weight of silicon oxide accounted for 45.8%, and the weight of alumina accounted for 11.5%) to obtain 103.9g of a mixed material. The mixture was placed in a tubular furnace for heating at a heating rate of 7°C / min, and reduction smelting was carried out at a temperature of 1600°C and an argon atmosphere for 150 minutes. After the reaction was completed, the cooling rate was 7°C / min, and the mixture was cooled to room temperature. The sample was taken out to obtain 12.2g of alloy and 64.4g of slag, respectively. 27.3g of smoke dust obtained by volatilization was collected on the inner wall of the reaction tube. The smoke dust was dissolved and leached with 200mL of distilled water. The reaction temperature of the dissolution and leaching was 40°C, the stirring rate was 800rpm, and the reaction time was 2 hours. The solution was then heated to 90°C, 0.8g of sodium hydroxide was added to a pH value of 13, and manganese hydroxide precipitate was obtained by filtration. Saturated sodium carbonate solution was continued to be added, and lithium carbonate precipitate was obtained by filtration after sufficient reaction.

[0036] The main components of the alloy are in weight percentage (wt.pct): Cu49.8, Co 11.2, Ni 35.0. The metal recovery rate is calculated to be: Cu 94%, Co 94.8%, Ni 92.6%. The main component of the obtained slag is calcium aluminum silicate, presenting a glassy slag phase, and the contents of Li and Mn in the slag are both less than 0.05wt.pct.

[0037] 2.3 g of manganese hydroxide was obtained by precipitation, and the calculated recovery rate of manganese was 96%; 4.9 g of lithium carbonate was obtained by precipitation, and the calculated recovery rate of lithium was 98%.

[0038] Example 4

[0039] After discharging, disassembling, crushing and grinding a waste lithium battery cell with a positive electrode material of NMC532, 41.0g of material (weight percentage (wt.pct) in the material: Li 0.90, Mn 2.10, Cu 5.99, Co 1.50, Ni 3.85) was obtained. This material was evenly ball-milled with 26.2g of calcium chloride powder, 31.7g of quartz powder and 16.4g of calcium oxide powder (the weight of calcium oxide in the slag system accounted for 42.8%, the weight of silicon oxide accounted for 45.8%, and the weight of aluminum oxide accounted for 11.4%) to obtain 115.3g of mixed material. The mixed material was placed in a tubular furnace for heating at a heating rate of 5°C / min, and reduced and smelted for 80min at a temperature of 1500°C and an argon atmosphere. After the reaction was completed, the cooling rate was 5°C / min, and it was cooled to room temperature, and the sample was taken out to obtain 12.5g of alloy and 75.8g of slag, respectively. 27g of smoke dust obtained by volatilization was collected on the inner wall of the reaction tube. The smoke dust was dissolved and leached with 200mL of distilled water. The reaction temperature of the dissolution and leaching was 20°C, the stirring rate was 400rpm, and the reaction time was 1 hour. The solution was then heated to 90°C, 0.8g of sodium hydroxide was added to a pH value of 13, and manganese hydroxide precipitate was obtained by filtration. Saturated sodium carbonate solution was continued to be added, and lithium carbonate precipitate was obtained by filtration after sufficient reaction.

[0040] The main components of the alloy are in weight percentage (wt.pct): Cu 50.3, Co 13.2, Ni 32.5. The metal recovery rate is calculated to be: Cu 91%, Co 95.5%, Ni 91.6%. The main components of the obtained slag are calcium aluminum silicate, presenting a glassy slag phase, and the contents of Li and Mn in the slag are both less than 0.05wt.pct.

[0041] 3.8 g of manganese hydroxide was obtained by precipitation, and the calculated recovery rate of manganese was 97%; 5.3 g of lithium carbonate was obtained by precipitation, and the calculated recovery rate of lithium was 97%.

[0042] Comparative Example 1

[0043] After discharging, disassembling, crushing and grinding a waste lithium battery cell with a positive electrode material of NMC111, 40.0g of material (weight percentage (wt.pct) in the material: Li 0.88, Mn 2.40, Cu 5.56, Co 2.50, Ni 2.51) was obtained. This material (the weight of aluminum in the material is 7.6g as alumina) and 30.2g of quartz powder and 28.5g of calcium oxide powder were evenly ball-milled (the weight of calcium oxide in the slag system accounted for 43.0%, the weight of silicon oxide accounted for 45.6%, and the weight of aluminum oxide accounted for 11.4%) to obtain 98.7g of mixed material. The mixed material was placed in a tubular furnace and reduced and smelted at a temperature of 1450°C in an argon atmosphere. After the reaction was completed, it was cooled to room temperature and the sample was taken out to obtain 10.1g of alloy and 88.6g of slag, respectively.

[0044] The main components of the alloy are in weight percentage (wt.pct): Cu 49.5, Co 23.4, Ni 22.5. The metal recovery rate is calculated to be: Cu 91%, Co 95.5%, Ni 91.6%. The main components of the obtained slag are calcium aluminum silicate, and Li and Mn are mainly in the slag.

[0045] Comparative Example 2

[0046] After discharging, disassembling, crushing and grinding a waste lithium battery cell with a positive electrode material of NMC811, 40.0g of material (weight percentage (wt.pct) in the material: Li 0.93, Mn 0.71, Cu 7.03, Co 0.71, Ni 5.46) was obtained. This material (the weight of aluminum in the material is 7.7g as alumina) and 30.9g of quartz powder and 29.8g of calcium oxide powder were evenly ball-milled (the weight of calcium oxide in the slag system accounted for 43.6%, the weight of silicon oxide accounted for 45.2%, and the weight of aluminum oxide accounted for 11.3%) to obtain 100.7g of mixed material. The mixed material was placed in a tubular furnace and reduced and smelted at a temperature of 1450°C in an argon atmosphere. After the reaction was completed, it was cooled to room temperature and the sample was taken out to obtain 13.2g of alloy and 87.5g of slag, respectively.

[0047] The main components of the alloy are in weight percentage (wt.pct): Cu 50.8, Co 5.0, Ni 39.0. The metal recovery rate is calculated to be: Cu 95%, Co 92%, Ni 94%. The main components of the obtained slag are calcium aluminum silicate, and Li and Mn are mainly in the slag.

[0048] Comparative Example 3

[0049] After discharging, disassembling, crushing and grinding a waste lithium battery cell with a positive electrode material of NMC622, 37.5g of material (weight percentage (wt.pct) in the material: Li 0.91, Mn 1.42, Cu 6.22, Co 1.39, Ni 4.44) was obtained. This material (the weight of aluminum in the material is 7.3g as alumina) and 29.0g of quartz powder and 29.8g of calcium oxide powder were evenly ball-milled (the weight of calcium oxide in the slag system accounted for 45.1%, the weight of silicon oxide accounted for 43.9%, and the weight of aluminum oxide accounted for 11.0%) to obtain 96.3g of mixed material. The mixed material was placed in a tubular furnace and reduced and smelted at a temperature of 1450°C and an argon atmosphere. After the reaction was completed, it was cooled to room temperature and the sample was taken out to obtain 11.3g of alloy and 85.0g of slag respectively.

[0050] The main components of the alloy are in weight percentage (wt.pct): Cu 49.9, Co 11.0, Ni 35.2. The metal recovery rate is calculated to be: Cu 94%, Co 93%, Ni 93%. The main components of the obtained slag are calcium aluminum silicate, and Li and Mn are mainly in the slag.

[0051] It can be seen from the results of the embodiments and comparative examples that, compared with the prior art, the method of the present invention can fully recover the lithium and manganese elements in waste ternary lithium batteries, and has a simple process, low cost, green and environmental protection, and is suitable for large-scale application.

Claims

1. A method for simultaneously recovering lithium, copper, cobalt, nickel and manganese from waste ternary lithium batteries, characterized in that: The following steps are involved: S1. The waste lithium battery is immersed in a saturated sodium chloride solution and discharged, and then disassembled, crushed and ground to obtain waste battery raw materials; S2. The waste battery raw material and the preset amount of calcium chloride, quartz stone, and limestone are ball-milled to obtain a mixture; S3. The mixture is heated and smelted in a protective gas atmosphere, and smoke, alloy phase and slag phase are collected; S4. dissolving and leaching the smoke using distilled water, and filtering to obtain a leachate and a leach residue; S5. The leachate is heated, sodium hydroxide is added, and manganese hydroxide precipitate is obtained by filtration, and sodium carbonate is added to the filtrate, and lithium carbonate precipitate is obtained by filtration; S6. Grind the alloy phase, digest it with hydrochloric acid and nitric acid, and then use extractants to extract copper ions and nickel and cobalt ions in the solution respectively.

2. The method for synchronously recovering lithium, copper, cobalt, nickel and manganese from waste ternary lithium batteries according to claim 1, characterized in that: In the step S1, the waste lithium batteries include NMC111, NMC622, NMC532, and NMC811 waste lithium batteries.

3. The method for synchronously recovering lithium, copper, cobalt, nickel and manganese from waste ternary lithium batteries according to claim 1, characterized in that: In step S2, the preset usage amount of calcium chloride is 2 to 3 times the sum of the molar numbers of lithium and manganese in the raw materials; the calcium chloride is an industrial-grade reagent; the preset usage amounts of quartz stone and limestone are added in a ratio of 40-60% by mass of calcium oxide, 35-45% by mass of silicon oxide, and 8-12% by mass of aluminum oxide in the calcium-silicon-aluminum slag system.

4. The method for synchronously recovering lithium, copper, cobalt, nickel and manganese from waste ternary lithium batteries according to claim 1, characterized in that: In the step S3, the protective gas is argon gas with a flow rate of 100 mL / min; the process conditions of the heating and smelting are: the smelting temperature is 1400-1600°C, the holding time is 80-150 min, and the heating rate is 5-10°C / min; after the heating and smelting is completed, it is cooled to room temperature at a cooling rate of 5-10°C / min, and smoke, alloy phase and slag phase are collected.

5. The method for synchronously recovering lithium, copper, cobalt, nickel and manganese from waste ternary lithium batteries according to claim 1, characterized in that: The slag phase is glassy, ​​wherein the contents of lithium, copper, cobalt, nickel and manganese metals are all less than or equal to 0.5wt.%, meeting the standards for making glass raw materials for building materials.

6. The method for synchronously recovering lithium, copper, cobalt, nickel and manganese from waste ternary lithium batteries according to claim 1, characterized in that: In the step S4, the liquid-to-solid ratio of smoke and distilled water is (5-15):1, and the liquid-to-solid ratio is the ratio of liquid volume mL to solid mass g; the process conditions of the dissolution and leaching are: reaction temperature of 20-40°C, stirring rate of 400-800rpm, and reaction time of 1-2h.

7. The method for synchronously recovering lithium, copper, cobalt, nickel and manganese from waste ternary lithium batteries according to claim 1, characterized in that: The step S5 specifically comprises: heating the leaching solution to 80-90° C., then adding sodium hydroxide to adjust the pH value to a pH greater than 12, filtering to obtain a manganese hydroxide precipitate and a filtrate; and then adding a saturated sodium carbonate solution to the filtrate, filtering to obtain a lithium carbonate precipitate after sufficient reaction.

8. The method for synchronously recovering lithium, copper, cobalt, nickel and manganese from waste ternary lithium batteries according to claim 1, characterized in that: In step S6, the extractant for copper ions is one or more of ketoximes or aldoximes; the extractant for nickel and cobalt ions is one or more of organic phosphine or amines.

Citation Information

Patent Citations

  • Methods for recovering valuable metals from spent lithium-ion batteries and / or their materials

    CN103526035B

  • Method for recovering lithium from waste lithium ion battery by pyrogenic process

    CN113061725A